COMPARATIVE ANALYSIS OF VOICE DISORDERS AND BODY PAIN IN EMERGENCY TELEOPERATORS - Santos, Cláudio da Cruz (2025)
Emergency teleoperators play a crucial role in society but face challenges related to vocal and physical health due to their working conditions. This observational, descriptive, analytical, cross-sectional, and quantitative study investigated the presence of voice disorders and bodily pain in 90 military and non-military teleoperators using specific questionnaires. The results revealed a higher prevalence of vocal problems, such as dry throat and hoarseness, and bodily pain, particularly in the neck and shoulders, among military teleoperators. Both groups reported dissatisfaction with their vocal quality and low rates of seeking medical or speech therapy assistance, highlighting the need for specialized attention. Significant differences between the groups were attributed to factors such as workload, length of service, and working conditions. It is concluded that an interdisciplinary approach is essential to prevent and treat voice disorders and bodily pain, thereby promoting the health and quality of life of these professionals.